Korelasi antara Profil Metabolik Laboratorium dan Tekanan Darah - Samara, Diana; Wartono, Magdalena; Kosasih, Adrianus (Fakultas Kedokteran Universitas Trisakti, 2024)
Background High blood glucose and cholesterol are risk factors for hypertension. This study aims to determine the correlation between blood glucose and cholesterol levels with blood pressure in the normal blood pressure (NBP), controlled hypertension (CHT), and uncontrolled hypertension groups (UHT). Methods The study used a cross-sectional design with analytic observations on subjects aged 36 years or older. Ninety-five subjects were divided into three groups: NBP, CHT, and UHT. Subjects were men and women, without chronic heart failure or chronic renal failure. Samples were taken by consecutive random sampling. Blood pressure, body mass index, random BG, and lipid profile (triglycerides, HDL, LDL, total cholesterol) were measured. Statistical test using Spearman correlation test with p-value <0.05 significantly. Results There were 95 subjects with a range age of 36-81 years old. There were 30 NBP subjects, 34 CHT subjects, and 31 UHT subjects. There was a weak positive correlation between HDL level and diastolic BP in the NBP group (r=0.391;p=0.032). There was no correlation between blood glucose and other lipid profiles with BP in the three groups. Conclusions The increase in HDL is accompanied by an increase in diastolic blood pressure in NT but not with random blood sugar and other lipid profiles in all three blood pressure groups.